A multidisciplinary non-invasive approach to monitor response to intravenous immunoglobulin treatment in neurodegenerative Langerhans cell histiocytosis: a real-world study - Trambusti, Irene; Barba, Carmen; Mortilla, Marzia; Rizzi, Susanna; Romano, Katiuscia; Coniglio, Maria Luisa; Lucenteforte, Ersilia; Tondo, Annalisa; Guerrini, Renzo; Sieni, Elena (Frontiers in Immunology, 2024)
have been suggested to prevent neurodegenerative progression. The aim of the study is to validate a standardized multidisciplinary diagnostic work-up to monitor the intravenous immunoglobulins (IVIG) treatment response and the natural course of the disease in untreated patients.Patients with abnormal somatosensory evoked potentials (SEPs) received monthly 0.5 g/kg IVIG. The diagnostic protocol included structural 3T MRI, neurological examination, brainstem auditory evoked potentials (BAEPs) and SEPs.Results: Twenty-two patients were followed for 5.2 years (median) from the first MRI evidence of ND-LCH. Eleven patients received IVIG for 1.7 years (median). At treatment start neurological examination was abnormal in 10 patients, of whom two had severe clinical impairment and four had abnormal BAEPs. At last follow-up, 1/11 remained stable and 7/11 improved, while worsening of neurological or neurophysiological findings, or both, occurred in 3/11. Risk factors for worsening were a severe clinical or MRI ND-LCH at treatment initiation and prolonged exposure to LCH. Of the 11 untreated patients, none improved and three worsened.Conclusions: Using a standardized diagnostic protocol, we demonstrated that IVIG treatment can lead to clinical stabilization or improvement in all pauci-symptomatic patients with an MRI grading of less than 4.